The distributional effects of the pension system reform in Poland - Elena Jarocinska; Anna Ruzik-Sierdzińska (IZA Journal of Labor Policy, 2023)
This paper quantifies the effect of Poland's 1999 pension reform on the inequality of future pension benefits. The reform increases inequality, both in the upper and lower parts of the distribution. The estimates, based on the 2012 Polish Household Budget Survey, show that the Gini coefficient reaches 0.27 once the full effect of the reform has materialized. Had the pre-reform system continued unchanged, the Gini coefficient would not be >0.19. The increased inequality of pension benefits is the result of the system gradually moving from a more redistributive defined benefit pension system to a system in which benefits are strongly linked to earnings. We show to what extent minimum pension benefits mitigate the increase in inequality under different scenarios.
Keywords: H55; J26; I38; 330; pension; inequality; replacement rate; minimum pension; microsimulation